An analysis of game design using graph-based substructure mining technique - Keattikorn Samarnggoon (2018)
To analyze and extract design of existing games is an interesting game research area but they are subjective due to different personal opinions. This paper presents method for finding central among personal vision of analyses by using graph-based representation of game design which allows the common to be found by the use of graph mining technique. The experimental result shows common graph which is compressed from diversity of game design graphs. © 2011 IEEE.